The commuting behavior and perception correlates of commuting trips: a comparative study on the Egyptian and migrant populations in Cairo and Alexandria - Randa Khalil; Dina Noseir; Yasmin Kandil; Ahmed Shehata; David G. Farid; Aly Elrefaei; Houshmand Masoumi (Renewable Energy and Sustainable Development, 2024)
The circumstances of commute travel behavior in a large part of developing countries, particularly in the Middle East and North Africa as well as the preferences of the main populations and the recent migrants are unclear. Thus, this study attempts to investigate the behaviors and preferences of commuters in Cairo and Alexandria, Egypt focusing on the Egyptian and non-Egyptian demographic groups. Two research questions were answered in this paper: (1) Are there significant differences between the commuting characteristics of Egyptians and non-Egyptians? (2) What are the subjective public transport use correlates of commute trip generation among Egyptians and non-Egyptians? Mann-Whitney U test and Ordinary Least Square models were applied to answer these questions based on the primary, disaggregate data of 1,810 face-to-face interviews (1,193 in Cairo and 617 in Alexandria) conducted from Nov. 2022 to May 2023. The results show a significant difference between the commuting variables of Egyptians and non-Egyptians in the sample, including their commute trip generation, commute trip time on weekdays, ideal commute trip time per day, satisfaction with commuting, willingness to spend time in commuting, and commuting expenses per month. When controlling for age, household size, and car ownership, four variables related to public transportation use significantly define the commute trip generation of both Egyptian and non-Egyptian groups. These variables include evaluation of the quality of buses and minibuses, perceived security when using public transportation, perceived security when uniformed guards or security forces are near the PT station/stop, and perceived security when the stations/stops are well-lit. These results can be used for better urban and mobility policymaking in the countries of the Middle East and North Africa.    Received: 30 November 2024 Accepted: 12 March 2024 Published: 22 May 2024